1911 Fla. Laws 268-69 - (:unkn) unknown (My University, 1911)
An Act Regulating the Manner of Catching Fish in the Fresh Water Lakes and Streams of Leon County, and Providing Punishment for Violations of this Act, ch. 6283, § 1: Prohibited fishing in the freshwater lakes and steams of Leon county with any seine, net, basket, trap, gun speer or gig. Violators guilty of a misdemeanor.
Keywords: FISHING REGULATION